Quellen zur jüdischen Familiengeschichtsforschung im Staatsarchiv Hamburg. Ein Wegweiser für die Spurensuche - Sielemann, Jürgen (Veröffentlichungen aus dem Staatsarchiv der Freien und Hansestadt Hamburg, 2015)
The archival material on the history of the Jewish communities of Hamburg which had been devastated during the Nazi era has been largely preserved. It allows in-depth family history and biographical research in numerous collections of the State Archives of Hamburg. The purpose of this guide is to promote the search for traces aces of the Jews of the past centuries. iNumerous examples provide an insight into the situation of Hamburg Jews during the past centuries.